A binary formulation for distribution reliability optimization considering substation bus schemes and outages in the subtransmission network, substations, and distribution feeders - Tarnate, Wilbert Rey D. (College of Engineering, University of the Philippines Diliman, 2013)
Existing methodologies for distribution reliability optimization have separately optimized feeder device locations and substation bus schemes. In this thesis a methodology that combines these two sub-problems is developed. The methodology uses Failure Modes and Effects Analysis (FMEA) to consider the probability of outages in the loop-type subtransmission network, in the distribution substations, and in the radial distribution feeders. Moreover, out methodology defines the formulations of System Average Interruption Frequency Index (SAIFI), System Average Interruption Duration Index (SAIDI), Average System Interruption Frequency Index (ASIFI), Average System Interruption Duration Index (ASIDI), and Cost Index that are explicitly expressed as functions of recloser locations, normally closed switch locations, fuse locations, and substation bus schemes. The bus schemes considered are the single-bus single-breaker, double-bus double-breaker, double-bus single-breaker, breaker-and-a-half-bus, and ring bus. Sample optimization cases, where the optimal feeder device locations depends on whether the substation bus scheme is considered or not, highlight the impact of combining the sub-problems into a single optimization problem.